Paired domination in graphs: A survey and recent results - Desormeaux, Wyatt J.,; Henning, Michael A., (Utilitas Mathematica, 2014)
A set S of vertices in a graph G is a paired dominating set if every vertex of G is adjacent to a vertex in S and the subgraph induced by S contains a perfect matching (not necessarily as an induced subgraph). The minimum cardinality of a paired dominating set of G is the paired domination number of G. This paper presents a survey of selected results on paired domination through 2013.